LINGUOPOETICS OF FAIRY TALES IN UZBEK, ENGLISH, KARAKALPAK FOLKLORE - Sarbinaz Khojabekova; T. Kerwenov (Journals Park Publishing, 2022)
Due to the fact that artistic texts often reveal the possibilities of the figurativeness and expressiveness of our language, it is important to study the participation of linguistic means in these texts in stylistic and linguopoetic aspects. Therefore, in Uzbek linguistics, a number of works have been created. The article provides the importance of linguapoetics on linguistics.
Keywords: Linguopoetics, a language of artistic work, ideological and artistic content, comparative analysis.